Hypertensive Crisis-Related Hospitalizations and Subsequent Major Adverse Cardiac Events in Young Adults with Cannabis Use Disorder: A Nationwide Analysis - Rupak Desai; Akhil Jain; Waleed Sultan; Zainab Gandhi; Athul Raj Raju; Vivek Joseph Varughese; Geethu Jnaneswaran; Charu Agarwal; Bisharah Rizvi; Zeeshan Mansuri; Puneet Gupta; Gautam Kumar; et al. (Medicina, 2022)
Background and Objectives: With the growing recreational cannabis use and recent reports linking it to hypertension, we sought to determine the risk of hypertensive crisis (HC) hospitalizations and major adverse cardiac and cerebrovascular events (MACCE) in young adults with cannabis use disorder (CUD+). Material and Methods: Young adult hospitalizations (18–44 years) with HC and CUD+ were identified from National Inpatient Sample (October 2015–December 2017). Primary outcomes included prevalence and odds of HC with CUD. Co-primary (in-hospital MACCE) and secondary outcomes (resource utilization) were compared between propensity-matched CUD+ and CUD- cohorts in HC admissions. Results: Young CUD+ had higher prevalence of HC (0.7%, n = 4675) than CUD- (0.5%, n = 92,755), with higher odds when adjusted for patient/hospital-characteristics, comorbidities, alcohol and tobacco use disorder, cocaine and stimulant use (aOR 1.15, 95%CI:1.06–1.24, p = 0.001). CUD+ had significantly increased adjusted odds of HC (for sociodemographic, hospital-level characteristics, comorbidities, tobacco use disorder, and alcohol abuse) (aOR 1.17, 95%CI:1.01–1.36, p = 0.034) among young with benign hypertension, but failed to reach significance when additionally adjusted for cocaine/stimulant use (aOR 1.12, p = 0.154). Propensity-matched CUD+ cohort (n = 4440, median age 36 years, 64.2% male, 64.4% blacks) showed higher rates of substance abuse, depression, psychosis, previous myocardial infarction, valvular heart disease, chronic pulmonary disease, pulmonary circulation disease, and liver disease. CUD+ had higher odds of all-cause mortality (aOR 5.74, 95%CI:2.55–12.91, p < 0.001), arrhythmia (aOR 1.73, 95%CI:1.38–2.17, p < 0.001) and stroke (aOR 1.46, 95%CI:1.02–2.10, p = 0.040). CUD+ cohort had fewer routine discharges with comparable in-hospital stay and cost. Conclusions: Young CUD+ cohort had higher rate and odds of HC admissions than CUD-, with prevalent disparities and higher subsequent risk of all-cause mortality, arrhythmia and stroke.